"This thing of testing our blood is really very important": a qualitative study of primary care laboratory services in Tete Province, Mozambique. Issue 1 (December 2016) - Tadeu, Benvindo; Geelhoed, Diederike
Abstract Background Laboratory services are essential for diagnosis and management of patients, and for disease control, and should form an integral part of primary health services capable of contributing to Universal Health Coverage. Nevertheless, they remain among the most neglected health services in resource-poor countries, including Mozambique. The Health Directorate of Tete Province, Mozambique, developed this study to analyse the role and perceived impact of laboratory services in primary healthcare on access, perceived service quality and disease control. Methods Qualitative research was done in three primary health facilities with and three without a laboratory in Tete Province, purposively sampled for their available services, accessibility and size. The role of the laboratory in primary health care was explored by reviewing documents, including records and monthly reports, interviews with clinicians, laboratory technicians and key informants (community leaders), and through focus group discussions with beneficiaries. Numeric data were summarized in Microsoft™ Excel. Qualitative data were analysed for content within generated categories, interpreted within the concept of Universal Health Coverage, cross validated between the researchers. Results The results showed a greater use of health services, with more frequent diagnosis and monitoring of prevalent diseases, in facilities with a laboratory as compared with facilities without. Clinicians, patients and community leaders in facilities with a laboratory perceived an improved possibility of diagnosing and treating prevalent diseases, resulting in greater satisfaction with the provided services. Laboratory technicians confirmed that patients appreciated having access to laboratory tests. Clinicians, patients and community leaders in facilities without a laboratory protested its lack, claiming that it increased the likelihood of costly referrals, delays and even deaths. Conclusions The study concluded that the laboratory plays an important role in primary level health facilities, as it is associated with greater utilization and perceived higher quality of services. Lack of a laboratory hampers patient management, disease control and financial risk protection. Expansion of the clinical laboratory system at primary level health facilities should be a properly funded priority of the national health system in Mozambique and similar countries.